Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia - Wibowo, Kunto; Johnson, Jeffrey W.; Motomura, Hiroyuki (Zootaxa, 2019)
The new, small-sized scorpionfish, Scorpaena regina, is described on the basis of 59 specimens from the east coast of Queensland, Australia, from depths of 2–57 m. The new species is most similar to the southwestern Pacific species, S. bulacephala and the Hawaiian endemic S. colorata, all three species being distinguished from all other Indo-Pacific species of Scorpaena by the following combination of characters: exposed cycloid scales covering the anteroventral surface of the body and pectoral-fin base, the lateral surface and dorsal margin of the lacrimal without spines, and the lateral surface of the maxilla without longitudinal ridges. The new species differs from S. bulacephala and S. colorata in having lower numbers of pectoral-fin rays, scale rows below the lateral line, and total gill rakers [13–17 (mode 16), 11–14 (12), and 13–17 (14 or 15), respectively], a simple anterior lacrimal spine, posterior tip of the pectoral fin (seventh or eighth ray longest) not reaching to vertical through first anal-fin spine, smaller body size (maximum size 64.5 mm SL), and shallower habitat (2–57 m). Morphological ontogenetic changes in the relative lengths of some body proportions in the new species are also discussed.